Improving EFL Students' Vocabulary in a Rural Area through Scrabble with Crossword Picture Puzzle - Diana Fauzia Sari; Yunisrina Qismullah Yusuf; Sri Wahyuni; Patcharin Kangkha (Journal of English Education and Teaching, 2023)
There are still many EFL students in Indonesia who face struggles in learning English, especially in memorizing vocabulary. This is prominent in particular to students who reside in rural areas, where besides school facilities are limited, motivation is also among the factors for their depleted motivation to learn English. The students in one of the senior high schools in Sabang island, Aceh, Indonesia, still strain when dealing with this subject. To solve the problem, a game insinuated to improve their vocabulary is the scrabble with crossword picture puzzle. This game demands cooperation of students to work together with their peers in a group in an entertaining way. This research employed the quantitative approach by experimental teaching. The sample of study of were 25 students in the experimental class and 26 students in the control class. Purposive sampling was used in which these two classes had most students with the lowest English scores among the other tenth grade students. The results of the t-score showed that there was a difference between the scores of the pre-test and the post-test of the experimental (4.23) and control classes (3.59). This proved that the used of scrabble with crossword picture puzzle game gave a significant improvement on students’ vocabulary. The application of this game made the students in the experimental class be more active, communicative, and challenging during learning process compared to the control class.